Turner Syndrome: Case Report - Oliveira Alves, Pollyana Cassimiro (2009)
lntroduction: Turner syndromeis a chromosomopathy that affects women, it is distinguished by the partial or complete absence of the X chromosome, accompanied by a combination of characteristic phenotypic features including the presence of short stature, sexual infantiilsm, ovarian dysgenesisand major and minor malformations. Objective: To describe a case of Turner syndrome.Method: Review of medical record.Case report: A 2-year-old girl with recurrent ear infections history and hypertrophy of adenoid,slymphedema of extremities at birth, beyond the following physical characteristics: growth retardation, low posterior hairline, pterigium coli, short neck, micrognathia, inner canthal folds and widely spaced nipples. The diagnosis was confirmed by the quantitative fluorescent polymerase chain reaction. Thereafter the patient was evaluated for the presence of associated cardiac and renal malformations that were excluded. At thistime she was in multidisciplinary monitoring.Conclusion: This report is an opportunity for discussion of clinical manifestations, diagnostic methods, follow up, and therapeutic strategies for Turner syndrome.